2001
DOI: 10.1007/s00439-001-0638-6
|View full text |Cite
|
Sign up to set email alerts
|

The mutation spectrum of the facilitative glucose transporter gene SLC2A2 (GLUT2) in patients with Fanconi-Bickel syndrome

Abstract: We report a total of 23 novel mutations of the SLC2A2 ( GLUT2) gene in 49 patients with a clinical diagnosis of Fanconi-Bickel syndrome (FBS). Molecular genetic analysis has now been performed in more than 50% of the 109 FBS cases from 88 families that we have been able to locate world-wide since the original report in 1949. In these 49 patients, 33 different SLC2A2 mutations (9 missense, 7 nonsense, 10 frameshift, 7 splice-site) have been detected. Thus, our results confirm that mutations of SLC2A2 are the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(102 citation statements)
references
References 28 publications
5
95
1
Order By: Relevance
“…FTT and/or hepatomegaly, prominent fluctuations in blood glucose levels, and proximal tubulopathy were found at presentation or during diagnosis or both in all our patients, similar to other series of FBS (Santer et al , 2002b. Although there were only mild differences in age at diagnosis, skeletal involvement ranged from none to radiological and/or clinical signs of rickets and osteopenia.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…FTT and/or hepatomegaly, prominent fluctuations in blood glucose levels, and proximal tubulopathy were found at presentation or during diagnosis or both in all our patients, similar to other series of FBS (Santer et al , 2002b. Although there were only mild differences in age at diagnosis, skeletal involvement ranged from none to radiological and/or clinical signs of rickets and osteopenia.…”
Section: Discussionsupporting
confidence: 86%
“…Signs and symptoms of FBS begin in infancy and include failure to thrive (FTT), hepatomegaly, hypophosphatemic rickets, and short stature (Santer et al 2002b). Biochemically, the disease is characterized by a general renal proximal tubular defect (glycosuria, bicarbonate wasting, aminoaciduria, renal tubular acidosis, hyperphosphaturia) and carbohydrate abnormalities that include postprandial hyperglycemia, fasting hypoglycemia, and hypergalactosemia (Odièvre et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first mutation in the SLC5A2 gene, positioned in 16p11.2, was reported by Santer et al (43), and more case series have confirmed that mutations in SLC5A2 are indeed responsible for the large majority of cases of FRG (44 -46). Additional support has come from several case reports (47-51).…”
Section: Molecular Geneticsmentioning
confidence: 88%
“…We then performed mutation analysis in patients with isolated, massive glucosuria. It turned out that homozygosity or compound heterozygosity for SGLT2 mutations may account for this condition, which was reported in abstract form in the same year (7). On the basis of these reports, a single patient with glucosuria and homozygosity for an SGLT2 mutation has meanwhile been published (8).…”
mentioning
confidence: 99%